PENGARUH PEMBIAYAAN MURABAHAH DAN MUDHARABAH TERHADAP LABA BERSIH PT. BPRS HAJI MISKIN PANDAI SIKEK KEC. X KOTO KABUPATEN TANAH DATARSUMATRA BARAT - Juniatul Adawiyah Tanjung; Cahya Agung Mulyana (Jurnal Ekonomi dan Bisnis, 2025)
This research aims to try and analyze the Net Profit of BPRS Haji Poor Smart Sikek. There are also several aspects analyzed that influence Net Profit, namely Murabahah and Mudharabah Financing. This research uses a quantitative approach using inferior information, namely information obtained from the Financial Services Authority's Sharia Banking Statistics (SPS OJK) based on monthly information for the period 2019-2022. The information collection instrument is based on BPRS Haji Miskin Information and the Financial Services Authority (OJK). ). The information analysis procedure used in this research is Multiple Linear Regression Analysis. The research results of partial multiple linear regression experiments prove that Murabahah Financing with a significant figure of 0.008, Mudharabah Financing with a significant figure of 0.111, has an important influence on Net Profit. Simultaneously, the totality of free elastics has an important impact on Net Profit, namely a significant number of 0.000≤ 0.05.